2020
DOI: 10.1111/jcmm.15261
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HOTTIP facilitates the stemness of breast cancer via regulation of miR‐148a‐3p/WNT1 pathway

Abstract: Emerging evidence suggests that dysregulation of long non‐coding RNA (lncRNA) plays a key role in tumorigenesis. The lncRNA, HOXA transcript at the distal tip (HOTTIP), has been reported to be up‐regulated in multiple cancers, including breast cancer, and is involved in various biological processes, including the maintenance of stemness. However, the biological function and underlying modulatory mechanism of HOTTIP in breast cancer stem cells (BCSCs) remains unknown. In this study, we found that HOTTIP was mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…In 2007, Li et al 37 firstly identified pancreatic CSCs using CD44 (+)CD24(+)ESA(+) as surface markers. Since then, pancreatic CSCs have been recognized in succession by using various surface markers, including CD133, 29 CD44, 38 CD24, c‐met and ALDH 39 . In the present study, we identified pancreatic CSCs using CD133 as a surface marker and found that the proportion of CSCs in PC cells was significantly elevated as to normal HPDE cells.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In 2007, Li et al 37 firstly identified pancreatic CSCs using CD44 (+)CD24(+)ESA(+) as surface markers. Since then, pancreatic CSCs have been recognized in succession by using various surface markers, including CD133, 29 CD44, 38 CD24, c‐met and ALDH 39 . In the present study, we identified pancreatic CSCs using CD133 as a surface marker and found that the proportion of CSCs in PC cells was significantly elevated as to normal HPDE cells.…”
Section: Discussionmentioning
confidence: 51%
“…miR‐148a has been confirmed to be involved in the maintenance of CSC‐like properties of hepatocellular carcinoma 20,21 . Li et al 38 demonstrated that miR‐148a‐3p is dramatically decreased in breast cancer stem cells and could be regulated by HOTTIP to suppress the stemness of breast cancer stem cells. Similarly, our data showed that miR‐148a‐3p was significantly down‐regulated, whereas the CSC markers, including CD133, Nanog, Oct4 and Sox2, were up‐regulated in pancreatic CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of HOTTIP correlates with the expansion of breast CSCs (BCSCs) and the expression of the stem cell markers, OCT4 and SOX2 . Han et al [ 66 ] demonstrated a reduced expression of differentiation markers, such as CK18 and CK14 and that miR-148a inhibits BC cell migration and invasion by directly targeting Wnt1. Moreover, it has been reported that HOTTIP controls miR-148a-3p by acting as a competing endogenous RNA (ceRNA).…”
Section: Canonical Wnt Pathway and Bcmentioning
confidence: 99%
“…Moreover, it has been reported that HOTTIP controls miR-148a-3p by acting as a competing endogenous RNA (ceRNA). Thereby, HOTTIP promotes expansion of CSCs in vitro and tumorigenesis in vivo by regulating the miR-148a-3p/Wnt1/β-catenin axis [ 66 ]. These data are summarized in Table 2 .…”
Section: Canonical Wnt Pathway and Bcmentioning
confidence: 99%
“…Moreover, lncRNA-Hh promotes the activation of the hedgehog signaling molecule Hh to upregulate SOX2 and OCT4 for BCSC maintenance 36 . The lncRNA HOTTIP regulates the miR-148a-3p/WNT1 pathway to maintain the CSC-like properties of BCSCs and facilitate BC growth 49 . Notably, NRAD1 was identified as the first lncRNA which can be activated by a CSC marker 50 .…”
Section: Lncrnas-mediated Bc Therapeutic Resistancementioning
confidence: 99%